Development Employee Payment Information System on CV Borneo Andeska Maja Samarinda - Andi Sari Putri; Emil Riza Putra; Ida Maratul Khamidah (TEPIAN, 2022)
This research is motivated by the unavailability of an employee payroll information system that facilitates data processing on CV Borneo Andeska Maja Samarinda in finance/treasury. Current the company from the finance/treasury section is still using Microsoft Excel in making employee salary recaps. Therefore the purpose of making a payroll information System in this study is to provide convenience and help reduce administrative costs or administrative costs and of course it can be a better information system. As for the development using the System Development Life Cycle (SDLC) with the PHP Programing language Framework Laravel. The data structure used is Entity Relationship Diagram (ERD) and Physical Diagram Model (PDM) and for the database using phpMySQL. The result of this study are expected to provide convenience for the company CV Borneo Andeska Maja Samarinda, especially in the finance department in terms of employee payroll which is carried out every month.